Antibiotic prescribing for upper respiratory tract infections and acute bronchitis: a longitudinal analysis of general practitioner trainees. (28th May 2022) - Baillie, Emma J; Merlo, Gregory; Magin, Parker; Tapley, Amanda; Mulquiney, Katie J; Davis, Joshua S; Fielding, Alison; Davey, Andrew; Holliday, Elizabeth; Ball, Jean; Spike, Neil; FitzGerald, Kristen; et al.
Abstract: Background: Most antibiotic prescribing for upper respiratory tract infections (URTIs) and acute bronchitis is inappropriate. Substantive and sustained reductions in prescribing are needed to reduce antibiotic resistance. Prescribing habits develop early in clinicians' careers. Hence, general practice (GP) trainees are an important group to target. Objectives: We aimed to establish temporal trends in antibiotic prescribing for URTIs and acute bronchitis/bronchiolitis by Australian GP trainees (registrars). Methods: A longitudinal analysis, 2010–2019, of the Registrars Clinical Encounters in Training (ReCEnT) dataset. In ReCEnT, registrars record clinical and educational content of 60 consecutive consultations, on 3 occasions, 6 monthly. Analyses were of new diagnoses of URTI and acute bronchitis/bronchiolitis, with the outcome variable a systemic antibiotic being prescribed. The independent variable of interest was year of prescribing (modelled as a continuous variable). Results: 28, 372 diagnoses of URTI and 5, 289 diagnoses of acute bronchitis/bronchiolitis were recorded by 2, 839 registrars. Antibiotic prescribing for URTI decreased from 24% in 2010 to 12% in 2019. Prescribing for acute bronchitis/bronchiolitis decreased from 84% to 72%. "Year" was significantly, negatively associated with antibiotic prescribing for both URTI (odds ratio [OR] 0.90; 95% confidence interval [CI]: 0.88–0.93) and acute bronchitis/bronchiolitis (OR 0.92; 95% CI: 0.88–0.96) on multivariable analysis, with estimates representing the mean annual change. Conclusions: GP registrars' prescribing for URTI and acute bronchitis/bronchiolitis declined over the 10-year period. Prescribing for acute bronchitis/bronchiolitis, however, remains higher than recommended benchmarks. Continued education and programme-level antibiotic stewardship interventions are required to further reduce registrars' antibiotic prescribing for acute bronchitis/bronchiolitis to appropriate levels. Lay Summary: It is well known that antibiotic consumption can cause antibiotic resistance. Most antibiotic prescribing happens in general practice. The common cold (upper respiratory tract infections) and cough (acute bronchitis) are 2 conditions that antibiotics are often prescribed for, but are not needed. There is considerable evidence that antibiotics do not help these conditions improve, and guidelines in Australia state that they are not a treatment option. General practitioners at the beginning of their career form prescribing habits early on. In light of the problem of antibiotic resistance, it is important to know how new doctors prescribe antibiotics, as they may do this for the rest of their career. We investigated their prescribing for the common cold and cough, from 2010 to 2019. We found that overall their prescribing has been declining over the last 10 years, but prescribing for cough is still too high. There needs to be more interventions in this group of doctors to reduce prescribing for this condition.